THE EFFECT OF USING VIDEO AS A MEDIA TOWARD STUDENTS’ SPEAKING SKILL - Lusi Marleni (Journal of English Language and Education, 2018)
This research aims to find out whether an effect of using video as a media toward students’ speaking skill at tenth grade of SMA 1 SALO, in academic year of 2017/2018. This research was classified as a quasi-experimental method. It involved 54 students of two groups. The experimental group was taught by using video and control group was taught using the conventional method. The data were obtained by using pre-test and post-test. After the data were tested and found to be normal but not homogeneous, the hypothesis was tested using the ANOVA test. The results of the research show that there is an effect in the speaking skill between the students who were taught by using video and those who were taught by using the conventional method. In ANOVA test it can be seen that (F-value = 53,209> F-table = 2,380 or sig = 0.000 < 0.05), and Significance (2-tailed) calculated (0.000) is smaller than 0.05. Therefore, the hypothesis of this study is accepted. In conclusion, the use of video as a media gave an effect to the students’ speaking skill in English teaching at SMA 1 SALO.